Influences of Social Support, Perceived Barriers, and Negative Meanings of Physical Activity on Physical Activity in Middle School Students - Hsu, Ya-Wen (J Phys Act Health, 2011)
BACKGROUND: A profound decline in physical activity occurs in puberty. This phenomenon is not well understood. Therefore, the purpose of this study is to examine associations between family/friend social support for physical activity, negative meanings of physical activity (NMPA), and internal/external barriers to physical activity with moderate to vigorous physical activity (MVPA), and sedentary and light behavior (SLB) in youth. METHODS: A total of 350 participants from 7 Los Angeles County middle schools participated in the study (62% Latina, 79% females). Hypothesized pathways were examined using structural equation modeling. Psychosocial variables and participation in MVPA and SLB were assessed by self-reported questionnaires. RESULTS: NMPA were related to lower levels of family/friend social support and greater internal/external barriers. Family social support was the only significant indicator of MVPA (β = 0.79). Low family social support was related to higher SLB (β = −0.25). CONCLUSIONS: Family social support seems crucial to promote MVPA and reduce SLB in adolescents and might be influenced by child’s feelings about physical activity. Future research should consider the interrelationship between psychosocial correlates of physical activity.